Sequential injection analysis (SIA)-chemiluminescence determination of indomethacin using tris[(2,2'-bipyridyl)]ruthenium(III) as reagent and its application to semisolid pharmaceutical dosage forms - Mervartová, Kateřina; Polášek, Miroslav; Calatayud, Jose Martinez (Analytica chimica acta, 2007)
Automated sequential injection (SIA) method for chemiluminescence (CL) determination of nonsteroidal anti-inflammatory drug indomethacin (I) was devised. The CL radiation was emitted in the reaction of I (dissolved in aqueous 50% v/v ethanol) with intermediate reagent tris(2,2'-bipyridyl)ruthenium(III) (Ru(bipy)(3)(3+)) in the presence of acetate. The Ru(bipy)(3)(3+) was generated on-line in the SIA system by the oxidation of 0.5mM tris(2,2'-bipyridyl)ruthenium(II) (Ru(bipy)(3)(2+)) with Ce(IV) ammonium sulphate in diluted sulphuric acid. The optimum sequence, concentrations, and aspirated volumes of reactant zones were: 15 mM Ce(IV) in 50mM sulphuric acid 41 microL, 0.5 mM Ru(bipy)(3)(2+) 30 microL, 0.4M Na acetate 16 microL and I sample 15 microL; the flow rates were 60 microLs(-1) for the aspiration into the holding coil and 100 microLs(-1) for detection. Calibration curve relating the intensity of CL (peak height of the transient CL signal) to concentration of I was curvilinear (second order polynomial) for 0.1-50 microM I (r=0.9997; n=9) with rectilinear section in the range 0.1-10 microM I (r=0.9995; n=5). The limit of detection (3sigma) was 0.05 microM I. Repeatability of peak heights (R.S.D., n=10) ranged between 2.4% (0.5 microM I) and 2.0% (7 microM I). Sample throughput was 180 h(-1). The method was applied to determination of 1 to 5% of I in semisolid dosage forms (gels and ointments). The results compared well with those of UV spectrophotometric method.
Keywords: Solvents; Indomethacin; Flow Injection Analysis; molekulární struktura; reprodukovatelnost výsledků; Financing, Organized; organokovové sloučeniny; rozpouštědla; Calibration; kalibrace; Luminescent Measurements; průtoková injekční analýza; luminiscenční měření; Reproducibility of Results; lékové formy; financování organizované; Organometallic Compounds; indomethacin; Dosage Forms; Molecular Structure